Nomogram for preoperative estimation risk of cervical lymph node metastasis in medullary thyroid carcinoma - Luo, Zhiyan; Hong, Yurong; Yan, Caoxin; Ye, Qin; Wang, Yong; Huang, Pintong (Frontiers in Oncology, 2022)
Objectives: Cervical lymph node metastasis (CLNM) is common in medullary thyroid carcinoma (MTC), but how to manage cervical lymph node involvement of clinically negative MTC is still controversial. This study evaluated the preoperative features and developed an ultrasound-based nomogram to preoperatively predict the CLNM of MTC. Materials and Methods: A total of 74 patients with histologically confirmed MTC were included in this retrospective study and assigned to CLNM-positive group and CLNM-negative group based on the pathology. The association between CLNM and preoperative clinical and sonographic characteristics (size, location, solid component, shape, margin, echogenicity, calcification, and extracapsular invasion of the tumor) were evaluated by the use of univariable and multivariable logistic regression analysis. A nomogram to predict the risk of the CLNM of MTC was built, and assessed in terms of discrimination, calibration and clinical usefulness. Results: The nomogram was based on three factors( tumor margin, US-reported suspicious lymph node and extracapsular invasion US features) and exhibited good discrimination with an AUC of 0.919 (95% CI, 0.856-0.932). The calibration curves of the nomogram displayed a good agreement between the probability as predicted by the nomogram and the actual CLNM incidence. Conclusions: We constructed and validated a US-based nomogram to predict an individual’s risk of CLNM in MTC patient, which can be easily evaluated before surgery. This model has the potential to assist clinical decision-making. Keywords: sporadic medullary thyroid carcinoma, cervical lymph node metastasis, ultrasonography, prevention lymph node dissection, nomogram